2005
DOI: 10.2174/138920305774933295
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Receptors in Gastrointestinal Smooth Muscle

Abstract: Endothelins (ETs) are a family of peptides with 21-amino-acid residues. ET-1 was identified as a potent vasoconstrictor produced by vascular endothelial cells. Three distinct isoforms of ET, i.e. ET-1, ET-2 and ET-3, have been found to exist in a variety of tissues. ET was later found to cause contraction as well as relaxation of smooth muscle in many physiologic systems. In the gastrointestinal tract, ET causes contraction and/or relaxation of the esophagus, stomach, ileum and colon. In the hepatobiliary syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
(184 reference statements)
1
9
0
Order By: Relevance
“…Implication here means that synthetic machinery for ET peptides, ET peptides themselves, and ET receptors have been localized to tissues in these systems, as well as demonstration that ET-1 causes a physiological function within that system. An incomplete list includes the cardiovascular (11,12,16,98), renal (35,58,87), central nervous (103), gastrointestinal (45), pituitary (61), adrenal (24,43,95,96), nasal (83), peripheral nervous (20,33,82), immune (76), hepatic (70), genitourinary (15), and endocrine systems (75).…”
mentioning
confidence: 99%
“…Implication here means that synthetic machinery for ET peptides, ET peptides themselves, and ET receptors have been localized to tissues in these systems, as well as demonstration that ET-1 causes a physiological function within that system. An incomplete list includes the cardiovascular (11,12,16,98), renal (35,58,87), central nervous (103), gastrointestinal (45), pituitary (61), adrenal (24,43,95,96), nasal (83), peripheral nervous (20,33,82), immune (76), hepatic (70), genitourinary (15), and endocrine systems (75).…”
mentioning
confidence: 99%
“…These fruit extracts may also interact with other non-adrenergic receptors that cause relaxation of the gastrointestinal (GI) smooth muscle, but were not included in this study. A family of peptides known as endothelins (ET) cause smooth muscle relaxation in the oesophagus, stomach and ileum through interaction with ET(A) or ET(B) receptors (Huang, 2005). Neurotransmitters such as adenosine, adenosine monophosphate (AMP), adenosine diphosphate (ADP), adenosine triphosphate (ATP) and other derivatives of these neurotransmitters, and nitric oxide are known to cause GI smooth muscle relaxation by stimulating purinoceptors (Burnstock, 2001;Giaroni et al, 2005;McDonnell et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Three isopeptides of ET, i.e., ET‐1, ET‐2, and ET‐3, have been identified. Endothelins act on cardiovascular, gastrointestinal, tracheal, urinary, and uterine smooth muscle 1,2 . In the gastrointestinal system, ET causes contraction or relaxation of the esophagus, lower esophageal sphincter, stomach, gallbladder, common bile duct, intestines, and internal anal sphincter 1–11 .…”
Section: Introductionmentioning
confidence: 99%
“…Endothelins act on cardiovascular, gastrointestinal, tracheal, urinary, and uterine smooth muscle 1,2 . In the gastrointestinal system, ET causes contraction or relaxation of the esophagus, lower esophageal sphincter, stomach, gallbladder, common bile duct, intestines, and internal anal sphincter 1–11 . Previous studies have demonstrated the involvement of ETs in many diseases, including pulmonary arterial hypertension, treatment resistant essential hypertension, proteinuric renal disease, and cancer 1,12–14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation